2021
DOI: 10.1177/08919887211023593
|View full text |Cite
|
Sign up to set email alerts
|

A Multicomponent Home-Based Intervention for Neuropsychiatric Symptoms in People With Dementia and Caregivers’ Burden and Depression: A 6-Month Longitudinal Study

Abstract: Objectives: Many people with dementia live in their home and require ongoing care, which is often provided by informal family caregivers. Thus, we examined the effectiveness of a multicomponent home-based intervention by evaluating its impact on a) neuropsychiatric symptoms of people with dementia and b) burden and depression of their caregivers. Methods: During the first 6 months of this prospective single-center study, we applied a home-based multicomponent intervention in 205 dyads of care-recipients and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…While no specific previous studies have been found on the effect of CRHT on caregiver burden, this result can be explained from different perspectives. Firstly, it is possible that the temporal distance between our measures (with a mean stay of around 23 days) is insufficient to assess the effect of the intervention on the most chronic and severe disorders such as SMD ( 30 ). Secondly, studies have found that the admission of another profile of chronically ill patients to an institution significantly reduces caregiver burden ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…While no specific previous studies have been found on the effect of CRHT on caregiver burden, this result can be explained from different perspectives. Firstly, it is possible that the temporal distance between our measures (with a mean stay of around 23 days) is insufficient to assess the effect of the intervention on the most chronic and severe disorders such as SMD ( 30 ). Secondly, studies have found that the admission of another profile of chronically ill patients to an institution significantly reduces caregiver burden ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dyadic stress management interventions for PLWD and their care partners often consist of several components and frequent interactions with health care professionals (eg, case management, advanced medical management, psychoeducation, cognitive behavioral training) [ 8 , 9 ]. While such interventions enable a variety of outcomes to be targeted, their complexity can increase burden on care partners who bear primary responsibility for engaging with the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…O desenvolvimento de estudos nessa temática ainda é escasso, contudo, algumas pesquisas de intervenção têm sido realizadas e mostram resultados semelhantes, conforme seguem as descrições.Intervenção multicomponente que incluiu a psicoeducação, a terapia cognitivo-comportamental e outras atividades, para auxiliar os cuidadores familiares principais de idosos com demência, foi realizada, durante seis meses, no domicílio desses cuidadores. Tal intervenção reduziu a gravidade dos SNPs dos idosos, bem como o desgaste emocional ou psicológico, a sobrecarga e os sintomas depressivos dos cuidadores(MOUGIAS et al, 2021).Outro estudo de intervenção psicossocial multicomponente, realizado em Manisa, na Turquia, revelou que houve redução do desgaste emocional ou psicológico, dos sintomas depressivos e ansiosos dos cuidadores de idosos com demência do grupo intervenção, como também houve melhora da QV, avaliada por meio do Medical Outcomes.Concluiu-se que a intervenção envolvendo educação e apoio aos cuidadores mostrou efeito positivo no desgaste emocional ou psicológico, na QV e nos sintomas depressivos e ansiosos dos cuidadores(UYAR et al, 2019).Um ensaio clínico randomizado investigou a efetividade de um programa, o "Tailored activity programoutpatient version" (TAP-O) sobre os SNPs do idoso e a sobrecarga do cuidador. Resultados mostraram que os idosos com demência que participaram do grupo intervenção apresentaram uma redução significativa dos SNPs, alucinação (p=0,04), agitação (p=0,03), ansiedade (p=0,02), agressividade (p=0,01), comportamento noturno e comportamento motor aberrante (p=0,02), como também os cuidadores participantes apresentaram redução da sobrecarga (p=0,003)(OLIVEIRA et al, 2019).…”
unclassified